2019
DOI: 10.3390/su11226250
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Satisfaction Scale of Basic Psychological Needs in Physical Education with the Incorporation of the Novelty in the Spanish Context

Abstract: The purpose of the study was to validate to the physical education context, the Spanish version of the Scale of the Satisfaction of Psychological Needs toward the Physical Education classes of Menéndez and Fernández-Rio, with the incorporation of the novelty, since they contemplated its inclusion. In this study, 1444 students participated (mean = 15.34, standard deviation = 1.12) from several schools in Almeria. To analyze the psychometric properties of the scale, several analyses were carried out. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
6
12
0
6
Order By: Relevance
“… González-Cutre et al (2016) showed through a confirmatory factor analysis that the need for novelty is a distinct construct to those of autonomy, competence, and relatedness. These results have coincided with recent findings by Trigueros et al (2019) in a study to validate the Spanish version of the Basic Psychological Needs Satisfaction Scale for Physical Education classes. The confirmatory factor analysis also showed the need for novelty as an independent factor.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“… González-Cutre et al (2016) showed through a confirmatory factor analysis that the need for novelty is a distinct construct to those of autonomy, competence, and relatedness. These results have coincided with recent findings by Trigueros et al (2019) in a study to validate the Spanish version of the Basic Psychological Needs Satisfaction Scale for Physical Education classes. The confirmatory factor analysis also showed the need for novelty as an independent factor.…”
Section: Introductionsupporting
confidence: 90%
“…R 2 = explained variances. Trigueros et al (2019), and González-Cutre et al (2020), where the types of autonomous motivation were positively predicted by the satisfaction of the four needs. This supports the idea that the need for novelty acts in synergy with the other three basic psychological needs, thus fulfilling one of the criteria established by Ryan and Deci (2017).…”
Section: Discussionmentioning
confidence: 93%
“…Containing 12 items, the BPNS-PE supported a three-factor structure and had high internal consistencies, which was recently confirmed by CFA in a Spanish [24] and English sample in PE [25]. Trigueros et al examined an adequate fit for a four-factor solution of the Spanish Scale of the Satisfaction of Psychological Needs in Physical Education [26], including a fourth subscale to assess the newly introduced need of novelty [27], and estimated an acceptable reliability by Cronbach's alpha of α > 0.70.…”
Section: Introductionmentioning
confidence: 81%
“…This is part of the version adapted to the Spanish PE (Trigueros et al, 2019d) context from the Scale of PNs Frustration in physical exercise (EFNP; Sicilia et al, 2013). The scale was composed of a total of 12 items, divided equally into three factors (autonomy, competence, and relatedness).…”
Section: Basic Psychological Needs Thwartingmentioning
confidence: 99%